EFFECTS OF ASSET STRUCTURE, OPERATING CASH FLOW, AND PROFITABILITY ON DEBT POLICY IN PROPERTY AND REAL ESTATE COMPANIES ON THE INDONESIA STOCK EXCHANGE PERIOD 2013-2017 - Peranginangin, Meilianta Br; Saragih, Cathrin Mutiara; Hantono, Hantono; Rahmi, Namira Ufrida; Guci, Siti Tiffany (Universitas Sam Ratulangi, 2018)
This study aims to determine the effect of asset structure, operating cash flow, and profitability on debt policy in property and real estate companies in the Indonesia Stock Exchange in 2013-2017. The analytical method used is multiple linear regression, F test and t test. The results of the analysis of this study indicate that the structure of assets, operating cash flows, and profitability have a simultaneous effect on debt policy. Meanwhile the analysis partially shows that the asset structure, operating cash flows, and profitability do not partially affect debt policy.